2021
DOI: 10.15244/pjoes/138211
|View full text |Cite
|
Sign up to set email alerts
|

A System Dynamics Model for Wood-Based Renewable Energy Production from Degraded Land Rehabilitation

Abstract: The trend of using wood biomass as a renewable energy source must be supported by a more extensive feedstock through the utilization of degraded land. However, not all regions have information on land potential in the provision of wood biomass. This study aims to develop a system dynamic model that can describe the potential of wood biomass production from degraded land rehabilitation. The main steps include problem identification, mapping causal loop diagrams, integrating mathematical models in a stock and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the same manner, Baydaş and Pamucar [43] applied seven multicriteria methods to evaluate the performance of companies in the financial sector, demonstrating that FUCA was the most simple methodology compared with the others they used (PROMETHEE, FUCA, TOPSIS, SAW, CODAS, COPRAS, and MOORA). On the other hand, Narendra et al [44] developed a model applying system dynamics to describe the wood biomass production potential starting from rehabilitating degraded lands. The result showed that all scenarios achieved reducing the degraded land area by 16%.…”
Section: Discussionmentioning
confidence: 99%
“…In the same manner, Baydaş and Pamucar [43] applied seven multicriteria methods to evaluate the performance of companies in the financial sector, demonstrating that FUCA was the most simple methodology compared with the others they used (PROMETHEE, FUCA, TOPSIS, SAW, CODAS, COPRAS, and MOORA). On the other hand, Narendra et al [44] developed a model applying system dynamics to describe the wood biomass production potential starting from rehabilitating degraded lands. The result showed that all scenarios achieved reducing the degraded land area by 16%.…”
Section: Discussionmentioning
confidence: 99%
“…The system dynamics method was proposed by Forrester in 1958 and is currently widely used to study various problems of supply chains, including inventory management [18], international supply chain management [19], demand amplification [20], supply chain design [21], information visibility [22], etc. It was originally applied to the study of industrial product supply chains, and was later introduced by some scholars to the study of energy supply chains, such as biomass [23][24][25], natural gas [26,27], oil [28][29][30] and electricity [31,32]. Among them, some national and regional research methods deserve attention.…”
Section: Research On System Dynamics In the Field Of Energy Supply Chainmentioning
confidence: 99%